Efficacy of Low-Level Laser Versus Topical Erythromycin 2% in the Treatment of Inflammatory Acne Vulgaris - Samar Saeed Ashmawy; Elham Mohamed Kassem; Shereen Farouk Gheida; Nahla Elsayed Ramzy (Mattioli1885, 2024)
Introduction: Acne vulgaris is a skin problem affecting many people of different ages. Despite many options that are available for treatment of acne vulgaris, many patients still respond inadequately to treatment. Phototherapy is one of the best acne treatment options. Objectives: It was to compare the efficacy of low-level laser therapy in treatment of inflammatory acne versus topical erythromycin 2% cream. Methods: This study included 40 patients (18 males, 22 females) with different clinical severities of acne vulgaris. All the participants underwent split-face treatment: one side with 8 treatments (twice per week) of a low-level continuous infrared diode laser (808 nm) wavelength and (500 Hz) frequency and the other side with topical erythromycin 2% twice daily (aknemycin cream 2%). Evaluation was done at start of sessions, 2 weeks after the end of sessions and 3 months after stoppage of treatment depending on: photographs, global evaluation of acne scale, and Indian acne association grading. Results: There was improvement of acne lesions on laser side and antibiotic side (assessed as non-inflammatory and inflammatory lesion counts). Laser side showed better results than antibiotic side. Patients were more satisfied with laser treatment due to minimal side effects and less relapse. Conclusion: A series of 8 treatments using low level continuous infrared diode laser represents a cheap, safe and effective non-invasive therapeutic option for acne vulgaris.